Construction and application of a solar radiation environment model in Chinese solar greenhouse - He, Fen; Ding, Xiaoming; Zhang, Guanshan; Gong, Binbin; Qi, Fei (International Journal of Agricultural and Biological Engineering, 2025)
In order to quantitatively analyze the light radiation environment inside Chinese solar greenhouse (CSG) and select reasonable building design parameters, a CSG solar radiation environment model reflecting various factors such as geographical location, outside solar radiation, orientation and building parameters, front roof shape, and covering materials was studied. The model considered the impact of both cloudy and sunny weather conditions on the inside solar radiation environment, and established a simulation calculation method for inside direct radiation and scattered radiation. When calculating solar scattered radiation, the ground reflected radiation and atmospheric longwave radiation was considered. When calculating the transmittance of covering material, a structural shading loss and dust film model was introduced to calculate its impacts on the transmittance. The model was validated experimentally in a CSG at Yongqing in Hebei Province, China. The results showed that the model can effectively simulate the solar radiation of various points such as the ground and wall in the greenhouse at any time, with an average relative error of 8.19% between the simulated and measured values. Based on the established model, the impact of the geographical location, azimuth angle, and building parameters of CSG on inside solar radiation were analyzed. The research results can provide theoretical references and relevant data for the wall and soil heat storage, crop planting, and energy balance of enclosure structures in CSG. Keywords: CSG, light radiation environment, solar radiation model, geographical location, azimuth angle, building parameterDOI: 10.25165/j.ijabe.20251805.9454Citation: He F, Ding X M, Zhang G S, Gong B B, Qi F. Construction and application of a solar radiation environment model in Chinese solar greenhouse. Int J Agric & Biol Eng, 2025; 18(5): 69–75.